Uji Penurunan Kandungan COD, BOD pada Limbah Cair Pewarnaan Batik Menggunakan Scirpus Grossus dan Iris Pseudacorus dengan Sistem Pemaparan Intermittent - Bieby Voijant Tangahu; Dwi Agustiang Ningsih (Teknik Lingkungan Universitas Islam Indonesia, 2016)
Mostly, batik industrial wastewater is produced from batik coloring process. One of this batik industry is located in Jetis, Sidoarjo since 1675. The wastewater produced from the coloring process in this location is directly dumped to Jetis river or drainage system around the area. One of the effective, efficient, and not costly wastewater treatment is by using phytotreatment process.Plants used in this research are Scirpus grossus and Iris pseudacorus. Both of this plants can grow in polluted environment and suitable to be used in wastewater treatment process. Moreover, both of these plants are semi aquatic plant that can grow in both wet and dry condition. Intermittent exposure system can be applied to increase the efficiency of the phytotreatment process for batik industry wastewater. This system connects plant and wastewater periodically through flood and drain cycle (F/D). This exposure can increase redox condition, so it can increase removal efficiency.The study variables used in this research are species variation of plants Scirpus grossus and Iris pseudacorus (single plant or combined plant) and intermittent exposure system variation, which is F/D 2:1 and F/D 1:2. The Primary parameter of this research is the concentration reduction of BOD, COD, and color. The secondary parameter such as plant morphology, wet weight, and dry weight, pH, and temperature.Preliminary research that has been done for this research is plant acclimatization and range finding test to determine the wastewater concentration. Phytotreatment test is conducted for 18 days in intermittent phase. The result shows that the best variable to remove pollutant is combined plant reactor with intermittent exposure of F/D 2:1 is able to remove 89% of COD and 97% of BOD.